Up, up, and away - Wadsworth, Ginger (Charlesbridge, 2009)
"Each spring hundreds of spiders hatch from their egg sacs and begin their struggle to survive. They must protect themselves not only from predators, but also from their very own siblings! Ginger Wadsworth and Patricia J. Wynne chronicle the real-life drama of one spider as she eats, grows, spins a dragline of silk, and soars up, up, and away to find a home of her own"--Publisher description.